Satisfaction with life as a criterion for the positive functioning of an individual (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article is devoted to the problem of life satisfaction as ageneralized assessment of the quality of a person’s existence. A theoreticaland methodological review of modern concepts of the phenomenon ispresented. An attempt is made of a detailed definitive analysis of theconcept of “satisfaction with life” in a system of related categories. Thespecificity of this assessment is determined, namely, as an integral indicatorof positive functioning. Some features of the structural model of satisfactionwith life are revealed, in particular, the role of cognitive and emotionalcomponents in the processes of consolidation and constructivization ofpositive existential experiences of a person. The system of factors thatphenomenalize emotionally — evaluative attitude to their life realization isallocated.
Keywords: life satisfaction; assessment of the quality of life; positive experiences; emotionally-evaluative attitude; psychological well-being; life fulfillment